Religious minorities in Turkey : Alevi, Armenians, and Syriacs and the struggle to desecuritize religious freedom /: Alevi, Armenians, and Syriacs and the struggle to desecuritize religious freedom. (2017) - Bardakçı, Mehmet Necmettin, 1957-; Freyberg-Inan, Annette; Giesel, Christoph; Leisse, Olaf
No abstract available